Assessing the Knowledge, Attitudes, and Practices of Students Regarding Ebola Virus Disease Outbreak - Kourosh HOLAKOUIE-NAIENI; Alireza AHMADVAND; Owais RAZA; Abraham ASSAN; Adel Hussein ELDUMA; Alieu JAMMEH; Aram Salih Mohammed Amin KAMALI; Ahang Abdullah KAREEM; Fatima Mahmud MUHAMMAD; Hasnain SABAHAT; Kabir Ozigi ABDULLAHI; Raeed Ahmad SAEED; et al. (Tehran University of Medical Sciences, 2015)
Background: The emergence and spread of Ebola outbreak is a growing problem worldwide, which represents a significant threat to public health. Evidence has shown that the level of knowledge, attitude, and practice of people in the society play major roles in controlling the spread of Ebola virus disease. This study was designed to determine knowledge, attitude and practice of students at School of Public Health, Tehran University of Medical Sciences towards Ebola. Methods: A cross-sectional survey was performed in Tehran, Iran in 2014 using a pretested self-administered questionnaire on a stratified sample of 400 students. Descriptive and multivariate analyses were used for statistical analysis. Results: All-in-all, 385 students returned the completed questionnaires making a response rate of 96.3%., 239 (62.2%) were females and 145 (37.8%) were males. The mean age of female and males were 28.44 and 30.3 years respectively. Of the 385students, 83 (21.7%) were studying at PhD level, 210 (55.0%) at Masters Level (including MPH) and 89 (23.3%) at Bachelors level. knowledge of the students regarding EVD transmission was lowest among students of Department of Occupational Health (50.0%), followed by Health Education and Promotion Department (33.3%). Virology Department recorded the highest percentage of students who had selected correct answers regarding EVD prevention (100.0%) Conclusion: These findings will aid in the assessment of the adequacy of current students' educational curriculum. Also, it will provide further insight in designing future multifaceted interventions to promote specific messages to change attitude and improve practice.   Keywords: Ebola, Outbreak, Tehran, Iran, Knowledge, Attitude, Practice, Students